Korrespondenzen der Goethezeit. edition und kommentar - Seckendorf, Leo von (Walter de Gruyter GmbH, 2014)
As the editor of poetic paperbacks and literary journals, Leo von Seckendorf (1775-1809) was in written correspondence with nearly all the great authors from the period of the Late Enlightenment, to the Classical and the Romance periods. This vastly diverse correspondence, which has previously been only partially accessible, offers extensive insight into the functionality of the literary market at around 1800. With over 300 letters from Seckendorf's extensive and wide-spread estate and including a detailed commentary, this edition recognizes for the first time the importance of this extrem.